Pemeriksaan Golongan Darah Di Sdn 137 Caramming Kab. Bulukumba - Islawati Islawati; Rahmat Aryandi (Jurnal Pengabdian Masyarakat, 2024)
This blood type education and examination activity aims to raise students' awareness of the importance of knowing their blood type from an early age. The activity was conducted on March 8, 2023, at SDN 137 Caramming, Caramming Village, Bontotiro District, with 28 students and 4 teachers participating. The methods used were lectures and simulations, covering materials on the definition of blood types, the types of blood groups, and the technique of blood type examination. The blood type examination was carried out using an agglutination method with anti-A, anti-B, anti-AB, and anti-D reagents to identify participants’ blood types and Rhesus factor. The results show high levels of enthusiasm among participants, reflected in students' active questioning about different blood types and their characteristics. The examination results indicated a variety of blood types among the participants, including types A, B, AB, and O, all with a positive Rhesus factor. In conclusion, this education and examination activity successfully increased students' knowledge of blood types, which is expected to foster early health awareness.